2012
DOI: 10.1016/j.comcom.2012.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Power consumption analysis of constant bit rate video transmission over 3G networks

Abstract: a b s t r a c tThis paper presents an analysis of the power consumption of video data transmission with constant bit rate over 3G mobile wireless networks. The work includes the description of the radio resource control transition state machine in 3G networks, followed by a detailed power consumption analysis and measurements of the radio link power consumption. Based on this description and analysis, we propose our power consumption model. The power model was evaluated on a smartphone Nokia N900, which follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, the lack of a constant power supply and limited battery capacity puts some restrictions on the overall power consumption of the sensor nodes. 26 Therefore, minimization of the power depletion in wearable nodes is a great challenge. Hence, a profound research in this field has concentrated on power consumption minimization.…”
Section: Energy Efficiency With Tpcmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lack of a constant power supply and limited battery capacity puts some restrictions on the overall power consumption of the sensor nodes. 26 Therefore, minimization of the power depletion in wearable nodes is a great challenge. Hence, a profound research in this field has concentrated on power consumption minimization.…”
Section: Energy Efficiency With Tpcmentioning
confidence: 99%
“…44 CBR transmission of VBR video can be performed with the optimal choice of buffer size, and the power consumption during CBR video transmission was analyzed. 26 This work describes the power consumption in the transmission part of the nodes, followed by a detailed analysis and measurements of the power consumption in the wireless on-body channel. Moreover, it was observed that much of the difficulty in determining WBSNs' battery lifetime comes from modeling the transceiver's power consumption as a function of time.…”
Section: Crcpmentioning
confidence: 99%
“…Falaki et al [2010] proposed the total of T1+T2 = 4.5 s based on their observation on packet inter-arrival time in traffic traces. Ukhanova et al [2012] also suggested aggressive timer configuration for CBR video transmission from mobile devices. Deng and Balakrishnan [2012] proposed to initiate FD dynamically instead of a fixed timeout value.…”
Section: Related Workmentioning
confidence: 99%
“…The power consumption of the DCH state is modelled as a linear equation using measurements on a Nokia N900 given the uplink and downlink power consumption for different of packet sizes [245]. Their device-specific model can be easily applied to model the different data rates in the DCH state for EnergyBox.…”
Section: Measurement-based Modelsmentioning
confidence: 99%
“…Puustinen et al [191] measure the impact of unwanted Internet traffic on the energy consumption for 3G and propose blocking traffic and fast dormancy as potential solution. Ukhanova et al [245] study the energy consumption of constant bit rate video communication over 3G and propose a RRC state machine parameter selection method to decrease the uplink energy consumption. Their work shows that by adapting the video quality and transmission power one can achieve energy savings.…”
Section: Cellular Communicationmentioning
confidence: 99%